Optimal contracts with privately informed agents and active principals - García, Diego (Journal of Corporate Finance, 2014)
This paper considers an optimal contracting problem between an informed risk-averse agent and a principal, when the agent needs to perform multiple tasks, and the principal is active, namely she can influence some aspect of the agency relationship on top of the contract itself (i.e. capital budgets, task assignments). The paper shows how asymmetric information makes incentives and investment decisions substitutes for the principal. This result yields novel implications for contracting models with moral hazard and asymmetric information, i.e., capital budgeting or external capital raising games.